Morphology and luminescence characteristics of yttriumdisilicate doped with yb3+, er3+(ho3+) and tm3+ - TAV, CUMALİ; BOYRAZ, CİHAT; EKMEKÇİ, METE KAAN; ERDEM, MURAT (Avestia Publishing, 2016)
[No abstract available]